Peer support to improve the secondary distribution of Internet-based HIV self-testing kits among men who have sex with men in Zhuhai, China - Lyu, Hang; Ni, Yuxin; He, Xi; Wang, Dongya; Yu, Xinxue; Tang, Weiming; Zhou, Yi (Frontiers in Public Health, 2025)
BackgroundSupport from peers is a commonly employed behavioral prevention approach aimed at key populations to enhance HIV prevention efforts. Internet-based HIV self-testing (HIVST) has been widely used among men who have sex with men (MSM) across China over the past few years.ObjectiveWe aimed to analyze the occurrence of Internet-based peer support and high-risk behaviors during the process of distributing HIVST kits among MSM.MethodsThe single-arm prospective cohort study was conducted among MSM in Zhuhai, China. The study utilized an HIVST online ordering system based on WeChat, which was developed by Xutong. MSM who ordered HIVST kits and distributed them to people in their network for self-testing were defined as index participants. People who received the kits from the index participants and provided testing results were defined as alters. Chi-squared tests were used to compare baseline and follow-up characteristics of the participants. Cramer’s V was used to quantify the level of association between the Internet-based HIVST and condomless anal sexual behaviors among index participants. Logistic regression analysis was used to evaluate factors associated with peer support among alter participants. A p-value <0.05 was regarded as statistically significant.ResultsA total of 288 index participants were included in the study, and they distributed HIVST kits to 478 alters. In the study, 84.0% (242/288) of the index participants reported that they provided peer support to their alters, and 87.4% (418/478) of the alters reported receiving peer support from the index participants. As for the alters, 19.9% (95/478) had sex with index participants on the day of HIVST. Among them, 24.2% (23/95) had sex after the HIVST and 72.6% (69/95) used a condom during sex. Index participants who had been asked for advice about HIV and other sexually transmitted infections were more likely to provide peer support to alters (OR: 1.85, 95% CI: 1.01–3.37).ConclusionThis study has enhanced our understanding of the occurrence of peer support and high-risk behaviors during the process of HIVST kits secondary distribution and provided evidence that Internet-based HIVST appears to be a promising approach for behaviors interventions among MSM.